Implementation of Strategic Management in Improving Organizational Performance in Manufacturing Companies - Nila Trisusanti; H. Arifuddin; Fauziah Umar (Indonesian Journal of Economics and Management, 2023)
This study aims to investigate the implementation of strategic management as an effort to improve organizational performance in manufacturing companies in Makassar. In the context of increasingly fierce competition and dynamic change, manufacturing companies need to adopt effective strategic approaches to gain competitive advantage. This study uses descriptive-qualitative research method by collecting data through interviews and direct observation in selected manufacturing companies.The results showed that the implementation of strategic management contributed positively to the improvement of organizational performance. In terms of strengths, manufacturing companies in Makassar have quality human resources and a good reputation in producing high quality products. However, some weaknesses such as dependence on the local market and limited financial resources need to be overcome. Opportunities that can be utilized are the growth of the global market and technological advances that can improve operational efficiency. Threats include intense competition and fluctuating raw material prices. Based on the findings, recommended strategies for improving organizational performance include market diversification, increased innovation, investment in new technology, and improved operational efficiency. The company also needs to strengthen cooperation with suppliers and monitor regulatory developments that may affect business operations. The implications of this study can serve as a guide for manufacturing companies in implementing strategic management to improve organizational performance.